STUDY ON HEAVY EQUIPMENT WORK PRODUCTIVITY IN SOIL SUB LOA KULU KUTAI KARTANEGARA REGENCY - ADIHARTA, THOPAN (KURVA S JURNAL MAHASISWA, 2014)
Productivity is the ability of the tool in a unit time (m3 / h), and heavy equipment is an important factor in the project, especially projects with large scale. The purpose of the use of heavy equipment is to enable people to do his job so that the desired results can be achieved more easily. Productivity tools depending on the capacity, cycle times instrument, appliance efficiency and compatibility of the use of tools.               PT. Bara Kumala Sakti (BKS) is one company that is engaged in the mining area of approximately 2,117. In the process of work stripping overburden (overburden), needs analysis and evaluation in the selection of mechanical device is very important to know whether the selection of tools - a mechanical device is correct - right so as to ensure the work performed can be run according to plan and on time with good result. With the selection of tools - a mechanical device that is right it will achieve optimal productivity tools, so that production targets can be achieved.               The data used are direct field observation data to the processes that occur in the field as a data cycle time and documentation. Other supporting data obtained from PT. Bara Kumala Sakti such as data units report data, production data plan, actual production data, and rainfall data.               From the results of calculations can be concluded that the productivity of excavator loading Hitachi ZX870-H series is 320.05 bcm / hour, production 123,667.32 bcm per month, and average productivity - average for conveyance Volvo A40E series was 87.53 bcm / hour , As for compatibility tool (match factor) in may MF 0.8. Because MF is less than one then the conveyance busy and excavator loading a lot of waiting for the waiting time per conveyance is 0.54 minutes. Number of conveyances required for 1 unit Excavator Hitachi ZX870 series-H is 4 units Volvo A40E Articulated Dump Truck.